A gradient iridescent ceramic tile and a preparation method and application thereof

CN118515502BActive Publication Date: 2026-10-30QINGYUAN GANI CERAMICS CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410340262.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2026-10-30
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

[0006]为了克服现有技术的不足,本发明针对在制备陶瓷砖时,直接使用拉长石原矿作为釉面原料,会有宝石蓝炫彩光泽消失现象,并且釉面有多种颗粒大小不一黄褐色斑点瑕疵及该瑕疵无法去除,降低陶瓷砖观感的缺点,提供一种渐变炫彩陶瓷砖及其制备方法和应用,通过对拉长石原矿进行加工提纯处理后,再应用到釉面的制备,在陶瓷砖表面呈现蓝宝石渐变炫彩金属光泽

Benefits of technology

[0033]1.本申请制备得到的陶瓷砖,干粒层的釉面采用透明熔块和炫彩颗粒组合,拉长石的熔点为1280-1500℃,在1220-1250℃辊道窑烧制,能保持烧制前炫彩颗粒原有的破碎肌理形状和状态不被熔化,透明熔块在此烧制温度下熔融形成透明的微晶层;透明熔块紧密包裹炫彩颗粒,在高温烧制过程中与炫彩颗粒熔融为一体,透明的微晶层越厚,拉长石颗粒的蓝宝石炫彩光泽三维立体效果越强,本申请的微晶层测试厚度为1-3mm,可呈现出很好的蓝宝石渐变炫彩金属光泽。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515502B_ABST
    Figure CN118515502B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of ceramic tiles, in particular to a kind of gradual change and application of a kind of dazzling ceramic tile and its preparation method.It is disclosed that a kind of gradual change and dazzling ceramic tile, including body, glaze layer being arranged on body, dry particle layer being arranged on glaze layer;The dry particle layer includes dazzling particle, transparent frit;The dazzling particle is obtained after feldspar ore is treated by treatment fluid;The treatment fluid includes the following raw materials: sulfuric acid, metal chloride solution, and the volume ratio of sulfuric acid and metal chloride solution is 1-2:1.The ceramic tile prepared in the application is applied to the preparation of glaze after the feldspar ore is processed and purified, and the ceramic tile surface presents a sapphire gradual change and dazzling metal luster.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic tile technology, and in particular to a gradient color ceramic tile, its preparation method, and its application. Background Technology

[0002] Currently, ceramic tiles on the market offer a variety of decorative colors and functional ink applications, capable of producing various gloss levels such as gloss, matte, pearlescent, and soft gloss. However, it's difficult to replicate the iridescent gradient luster of sapphire, which creates a gradient of vibrant blue metallic sheen as the angle of light changes. Current ceramic tile decorative effects utilize color pigments including cobalt blue, sea blue, peacock blue, and vanadium blue, lacking the iridescent gradient metallic texture of natural stone. Furthermore, they fail to exhibit the vivid and flexible changes in color and pattern, as well as the iridescent luster, that occur with varying light angles.

[0003] Labradorite, also known as spectral stone, is a type of feldspar between sodium feldspar and calcium feldspar. It has a melting point of 1280-1500℃, a vitreous luster, and contains special metallic elements that impede light propagation. Under different angles of sidelight, it emits a gradient of iridescent blue hues, resembling a gemstone. As the angle of light changes, the iridescent luster changes until it gradually disappears. The main reason for this iridescent luster is the sawtooth-like twinned thin-layer structure of the nearly parallel, tabular, fine-grained shale components within labradorite. This structure causes light interference, creating the unique iridescent blue luster.

[0004] Currently, there are no reports in the ceramics industry of researchers attempting to apply labradorite to the glaze of ceramic tiles to create a gem-like gradient and dazzling luster.

[0005] Therefore, this application provides a gradient color ceramic tile, its preparation method, and its application. Summary of the Invention

[0006] To overcome the shortcomings of existing technologies, this invention addresses the drawbacks of using labradorite ore directly as a glaze material in the preparation of ceramic tiles. These drawbacks include the loss of the sapphire blue luster, the presence of various yellowish-brown spots of varying particle sizes on the glaze surface that cannot be removed, and the reduced aesthetic appeal of the ceramic tiles. The invention provides a gradient shimmering ceramic tile, its preparation method, and its application. By processing and purifying the labradorite ore before applying it to the glaze preparation, a sapphire gradient shimmering metallic luster is achieved on the surface of the ceramic tile.

[0007] The technical solution adopted by this invention to solve its technical problem is:

[0008] The primary objective of this application is to provide a gradient color ceramic tile, comprising a bisque, a glaze layer disposed on the bisque, and a dry granule layer disposed on the glaze layer.

[0009] The dry granular layer includes iridescent particles and transparent frit;

[0010] The iridescent particles are obtained by crushing and treating labradorite ore with a processing solution.

[0011] The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1-2:1.

[0012] Preferably, the labradorite ore is crushed into 2-20 mesh flaky labradorite particles with a thickness of 1.5-3 mm. After the flaky labradorite particles are treated with a processing solution, iridescent particles are obtained.

[0013] More preferably, the treatment conditions for the treatment liquid are as follows: placing it in an ultrasonic container, heating it to 50-80°C, and stirring for 60-120 minutes.

[0014] Preferably, the concentration of the metal chloride solution is 0.5-3 mol / L.

[0015] More preferably, the solute in the metal chloride solution is any one or more of zinc chloride, magnesium chloride, and calcium chloride.

[0016] Preferably, the iron ion content in the iridescent particles is ≤0.04%.

[0017] Preferably, the transparent frit comprises, by weight, the following raw materials:

[0018] Potassium feldspar 14-30 parts, sodium feldspar 8-22 parts, kaolin 6-10 parts, calcined clay 4-12 parts, corundum 2-10 parts, diopside 6-10 parts, wollastonite 6-12 parts, lithium feldspar 8-14 parts, strontium carbonate 4-10 parts, zinc oxide 2-10 parts.

[0019] The second objective of this application is to provide a method for preparing gradient color ceramic tiles, comprising the following steps:

[0020] 1) Preparation of colorful particles

[0021] After the raw labradorite ore is crushed, it is treated with a processing solution to obtain iridescent particles;

[0022] 2) Preparation of transparent frit

[0023] Prepare the corresponding fine chemical raw material powders according to the weight composition of the transparent frit; mix the fine chemical raw material powders evenly and fire them in the frit furnace to form transparent frit particles;

[0024] 3) Apply dry granular layer

[0025] Mix the iridescent particles and transparent frit particles evenly in a certain proportion to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0026] 4) Firing

[0027] After the raw body with the mixture is applied is dried, it is fired in a roller kiln to obtain a semi-finished product of gradient colorful ceramic tile.

[0028] 5) Polishing

[0029] The semi-finished gradient color ceramic tile is polished to obtain the finished gradient color ceramic tile.

[0030] Preferably, in step 4), the firing temperature of the roller kiln is 1220-1250℃, and the firing cycle is 65-80min.

[0031] The third objective of this application is to provide an application for gradient color ceramic tiles, applying the aforementioned gradient color ceramic tiles to the decoration field.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The ceramic tile prepared in this application has a glaze surface of dry granule layer composed of a combination of transparent frit and iridescent particles. Labradorite has a melting point of 1280-1500℃ and is fired in a roller kiln at 1220-1250℃. This process preserves the original broken texture and shape of the iridescent particles before firing, preventing them from melting. The transparent frit melts at this firing temperature to form a transparent microcrystalline layer. The transparent frit tightly wraps around the iridescent particles and melts into one with them during the high-temperature firing process. The thicker the transparent microcrystalline layer, the stronger the three-dimensional effect of the sapphire iridescent luster of the labradorite particles. The tested thickness of the microcrystalline layer in this application is 1-3mm, which can exhibit a very good sapphire gradient iridescent metallic luster.

[0034] 2. The method for preparing gradient iridescent ceramic tiles shown in this application involves breaking labradorite particles into flaky feldspar particles with a thickness of 1.5-3 mm during the fine crushing stage. These particles are then mixed with transparent frit in a certain proportion and applied to the microcrystalline layer. The size of the gem-like luster area of ​​each iridescent particle can be controlled according to the size of the broken labradorite particles. The larger the flaky particles, the larger the area of ​​the gradient iridescent luster that each iridescent particle exhibits after polishing. Furthermore, the particle size can be randomly matched, resulting in a higher degree of realism compared to natural luxury stones.

[0035] 3. Preparation method of gradient iridescent ceramic tiles: After the unglazed ceramic tile is fired in a roller kiln, there is a slight unevenness between the iridescent particles and the microcrystalline layer. The surface of the semi-finished ceramic tile is matte and produces diffuse reflection. The gradient gloss effect of the iridescent particles is poor. Through rough polishing, medium polishing and fine polishing processes, the surface of the ceramic tile is polished and brightened. After treatment with super-clean and bright wax, the surface of the ceramic tile presents a perfect marble pattern. At the same time, when the angle of light irradiation rotates, the incident light of the iridescent particles will produce mutual interference, so that the iridescent particles will present a gradient sapphire iridescent metallic luster. Attached Figure Description

[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0037] Figure 1 This is a process flow diagram of the preparation method of the gradient color ceramic tile described in this application. Detailed Implementation

[0038] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.

[0039] As used herein, “and / or” includes all combinations of any one or more of the associated listed items. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used herein, the singular forms “a,” “an,” “an,” and “the” are also intended to include the plural forms unless the context clearly indicates otherwise. Further understanding is needed; when used in this specification, “comprising” designates the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or combinations thereof.

[0040] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Further understanding is that terms, such as those defined in common dictionaries, are interpreted in accordance with their meaning in the context of the relevant field and are not idealized or overly formal, unless expressly defined herein.

[0041] The exemplary invention described herein may suitably omit any one or more limiting elements, which are not specifically disclosed herein. Therefore, terms such as “comprising,” “including,” “containing,” etc., should be interpreted broadly and non-limitingly. Furthermore, the terminology used herein is for descriptive purposes without limitation, and it is unintentional to use terms that do not include any equivalent characteristics, but only to describe a portion of their characteristics; however, various modifications are possible within the scope of the invention according to the claims. Therefore, while the invention has been specifically disclosed through preferred embodiments and optional features, variations of the invention embodied by the modifications disclosed herein may be noted by those skilled in the art, and such modifications and variations are considered to be within the scope of the invention.

[0042] All raw materials or reagents used in the embodiments and comparative examples of this invention were purchased from mainstream manufacturers on the market. Those without specified manufacturers or concentrations are all analytical grade raw materials or reagents that are routinely available. There are no particular restrictions as long as they achieve the expected effect. The reaction vessels and rotary evaporators used in this embodiment were all purchased from major manufacturers on the market. There are no particular limitations as long as they achieve the expected effect. Where specific techniques or conditions are not specified in this embodiment, they should be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions.

[0043] The inventor discovered through numerous attempts at the firing process that when the dry granule layer is prepared by directly combining labradorite ore and frit, the sapphire blue iridescent luster of the dry granule layer disappears. Furthermore, the glaze surface of the dry granule layer has various yellow spots of different particle sizes that cannot be removed, thus lowering the grade of the ceramic tile product.

[0044] The inventors discovered that using ordinary labradorite ore as a carrier for iridescent stones, directly applied to the dry granule layer of the brick blank, results in iron oxide or other oxides adhering to the surface of the labradorite particles. When applied to the surface layer of the ceramic tile, these oxides react with oxygen and hydrogen sulfide in the kiln atmosphere during firing, generating yellowish-brown iron oxide and iron sulfide spots, affecting the aesthetics. Therefore, this application, through Experiment 1 and Experiment 2, removes iron impurities from the labradorite ore to obtain high-purity iridescent particles, which are then applied to the dry granule layer of the brick blank to prepare gradient iridescent ceramic tiles.

[0045] Experimental Study 1

[0046] A method for preparing iridescent particles includes the following steps:

[0047] 1) Take the blocky labradorite ore and perform preliminary washing with circulating water to wash away the mud and sand on the surface of the ore. Use a jaw crusher to crush it. The jaw crusher performs primary crushing and breaks it into 4-6 cm blocks of ore. Then, a second set of jaw crushers performs secondary crushing and breaks it into 2-3 cm pieces. Finally, it is further finely crushed into flaky particles of about 3-8 mm.

[0048] 2) The crushed labradorite particles are rinsed twice with circulating water to remove dust and impurities adhering to the surface of the crushed feldspar particles. At the same time, they are sieved with a rotary screen to filter out the rinsing water and particles that are not up to size during the crushing process. Flaky labradorite particles between 2 and 20 mesh are selected, dried, and used as spare materials.

[0049] 3) According to the volume ratio of sulfuric acid to metal chloride solution of 1-2:1, add 1-3 mol / L sulfuric acid to 0.5-3 mol / L metal chloride solution and mix to obtain a mixed solution; place the mixed solution in an ultrasonic container, add crushed and rinsed 2-20 mesh labradorite particles, turn on the stirring device, and obtain a stirred mixture.

[0050] 4) Heat the stirred mixture to 50-80℃ and stir it at 50-80℃ for 60-120 minutes to carry out the reaction. The stirring speed is 20-100 r / min. After the reaction is completed, cool it to room temperature to obtain the reacted mixture.

[0051] 5) After the reaction, the mixture is passed through a 30-mesh rolling sieve for solid-liquid separation. The separated solution is collected and processed to remove iron ions and adjust the pH value for recycling.

[0052] 6) The solid labradorite particles obtained from the mixture after the reaction are added to clean water and stirred and washed for 10-60 minutes. The water is then changed and stirred and washed again. The washing and stirring process is repeated three times. After draining the washing water, the feldspar particles are dried to obtain iridescent particles with iron impurities removed.

[0053] Specifically, in this application, the solute in the metal chloride solution can be zinc chloride, magnesium chloride, or calcium chloride. In the above-mentioned test process, zinc chloride is used, that is, 1L of sulfuric acid and 1L of zinc chloride solution are mixed, and then 500g of crushed labradorite particles are added. The concentrations of sulfuric acid and zinc chloride solution are adjusted, and the mixture is stirred and heated. In order to increase the concentration of each component in the mixture, the present invention can also directly add zinc chloride powder to the sulfuric acid solution for dissolution and mixing, so that the concentration of the metal chloride solution is maintained within the preferred concentration range, which is beneficial to improving the leaching rate of iron impurities.

[0054] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and comparative examples. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0055] This application provides, as follows: Figure 1 The method for preparing a gradient color ceramic tile includes the following steps:

[0056] Example 1

[0057] A method for preparing gradient color ceramic tiles includes the following steps:

[0058] 1) Preparation of colorful particles

[0059] Labradorite ore is crushed into 4-mesh labradorite particles. The labradorite particles are treated with a treatment solution and stirred at 30°C for 60 minutes at a stirring speed of 80 r / min. After rinsing and drying, iridescent particles are obtained. The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1:1; the concentration of sulfuric acid is 1.0 mol / L, and the concentration of metal chloride solution is 1.0 mol / L.

[0060] 2) Preparation of transparent frit

[0061] Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit.

[0062] The transparent frit, by weight, comprises the following raw materials:

[0063] Potassium feldspar 20 parts, sodium feldspar 19 parts, kaolin 10 parts, calcined clay 6 parts, corundum 5 parts, diopside 6 parts, wollastonite 10 parts, lithium feldspar 8 parts, strontium carbonate 8 parts, zinc oxide 8 parts.

[0064] 3) Apply dry granular layer

[0065] Mix the iridescent particles and transparent frit particles evenly in a certain proportion to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0066] 4) Firing

[0067] The unglazed body after applying the mixture is fired at 1230℃ for 65 minutes to obtain a semi-finished product of gradient colorful ceramic tile.

[0068] 5) Polishing

[0069] Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

[0070] Example 2

[0071] A method for preparing gradient color ceramic tiles includes the following steps:

[0072] 1) Preparation of colorful particles

[0073] Labradorite ore is crushed into 4-mesh labradorite particles. The labradorite particles are treated with a treatment solution and stirred at 80°C for 120 minutes at a stirring speed of 30 r / min. After rinsing and drying, iridescent particles are obtained. The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1:1; the concentration of sulfuric acid is 0.5 mol / L, and the concentration of metal chloride solution is 1 mol / L.

[0074] 2) Preparation of transparent frit

[0075] Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit.

[0076] The transparent frit, by weight, comprises the following raw materials:

[0077] Potassium feldspar 28 parts, sodium feldspar 16 parts, kaolin 9 parts, calcined clay 10 parts, corundum 3 parts, diopside 6 parts, wollastonite 10 parts, lithium feldspar 6 parts, strontium carbonate 8 parts, zinc oxide 4 parts.

[0078] 3) Apply dry granular layer

[0079] Mix the iridescent particles and transparent frit particles evenly to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0080] 4) Firing

[0081] The unglazed body after applying the mixture is fired at 1220℃ for 80 minutes to obtain a semi-finished product of gradient colorful ceramic tile.

[0082] 5) Polishing

[0083] Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

[0084] Example 3

[0085] A method for preparing gradient color ceramic tiles includes the following steps:

[0086] 1) Preparation of colorful particles

[0087] Labradorite ore is crushed into 4-mesh labradorite particles. The labradorite particles are treated with a treatment solution and stirred at 50°C for 60 minutes at a stirring speed of 80 r / min. After rinsing and drying, iridescent particles are obtained. The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1:1; the concentration of sulfuric acid is 2.0 mol / L, and the concentration of metal chloride solution is 1.5 mol / L.

[0088] 2) Preparation of transparent frit

[0089] Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit.

[0090] The transparent frit, by weight, comprises the following raw materials:

[0091] Potassium feldspar 22 parts, sodium feldspar 15 parts, kaolin 8 parts, calcined clay 10 parts, corundum 7 parts, diopside 6 parts, wollastonite 9 parts, lithium feldspar 10 parts, strontium carbonate 7 parts, zinc oxide 7 parts.

[0092] 3) Apply dry granular layer

[0093] Mix the iridescent particles and transparent frit particles evenly to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0094] 4) Firing

[0095] The unglazed body after applying the mixture is fired at 1230℃ for 75 minutes to obtain a semi-finished product of gradient colorful ceramic tile.

[0096] 5) Polishing

[0097] Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

[0098] Example 4

[0099] A method for preparing gradient color ceramic tiles includes the following steps:

[0100] 1) Preparation of colorful particles

[0101] Labradorite ore is crushed into 4-mesh labradorite particles. The labradorite particles are treated with a treatment solution and stirred at 40°C for 70 minutes at a stirring speed of 60 r / min. After rinsing and drying, iridescent particles are obtained. The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1:1; the concentration of sulfuric acid is 2.5 mol / L, and the concentration of metal chloride solution is 2 mol / L.

[0102] 2) Preparation of transparent frit

[0103] Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit.

[0104] The transparent frit, by weight, comprises the following raw materials:

[0105] Potassium feldspar 20 parts, sodium feldspar 17 parts, kaolin 8 parts, calcined clay 10 parts, corundum 7 parts, diopside 8 parts, wollastonite 9 parts, lithium feldspar 10 parts, strontium carbonate 6 parts, zinc oxide 5 parts.

[0106] 3) Apply dry granular layer

[0107] Mix the iridescent particles and transparent frit particles evenly to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0108] 4) Firing

[0109] The unglazed body after applying the mixture is fired at 1250℃ for 65 minutes to obtain a semi-finished product of gradient colorful ceramic tile.

[0110] 5) Polishing

[0111] Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

[0112] Example 5

[0113] A method for preparing gradient color ceramic tiles includes the following steps:

[0114] 1) Preparation of colorful particles

[0115] Labradorite ore is crushed into 4-mesh labradorite particles. The labradorite particles are treated with a treatment solution and stirred at 40°C for 70 minutes at a stirring speed of 80 r / min. After rinsing and drying, iridescent particles are obtained. The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1:1; the concentration of sulfuric acid is 3.0 mol / L, and the concentration of metal chloride solution is 3.0 mol / L.

[0116] 2) Preparation of transparent frit

[0117] Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit.

[0118] The transparent frit, by weight, comprises the following raw materials:

[0119] Potassium feldspar 30 parts, sodium feldspar 10 parts, kaolin 8 parts, calcined clay 9 parts, corundum 7 parts, diopside 6 parts, wollastonite 7 parts, lithium feldspar 10 parts, strontium carbonate 8 parts, zinc oxide 5 parts.

[0120] 3) Apply dry granular layer

[0121] Mix the iridescent particles and transparent frit particles evenly to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0122] 4) Firing

[0123] The unglazed body after applying the mixture is fired at 1240℃ for 75 minutes to obtain a semi-finished product of gradient colored ceramic tile.

[0124] 5) Polishing

[0125] Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

[0126] Comparative Example 1

[0127] The conditions in this comparative example are the same as those in Example 1, except that in step 1), the preparation of the iridescent particles involves crushing the labradorite ore into 4-mesh labradorite particles, washing and drying them directly without iron removal treatment to obtain iridescent particles; then, transparent frit is prepared in the same proportion as in Example 1, and the iridescent particles without iron removal are mixed with the frit particles in a certain proportion, a dry particle layer is applied to the brick blank, and the brick is fired and polished to obtain the finished gradient iridescent ceramic brick.

[0128] Comparative Example 2

[0129] The preparation steps and parameters in this comparative example are the same as those in Example 2. The difference is that in step 1), the preparation of the iridescent particles involves stirring the labradorite and the treatment liquid at a speed of 80 r / min, followed by rinsing and drying to obtain the iridescent particles. Then, transparent frit is prepared in the same proportion as in Example 2. The prepared iridescent particles and frit particles are mixed in proportion, a dry particle layer is applied to the brick blank, and the brick is fired and polished to obtain the finished gradient iridescent ceramic brick.

[0130] Comparative Example 3

[0131] The preparation steps and parameters in this comparative example are the same as those in Example 1. The difference is that in step 1), the preparation of the iridescent particles involves treating the labradorite particles with a treatment liquid at 20°C for 30 minutes at a stirring speed of 50 r / min, followed by rinsing and drying to obtain the iridescent particles. Then, transparent frit is prepared in the same proportion as in Example 1. The prepared iridescent particles and frit particles are mixed in proportion, a dry particle layer is applied to the brick blank, and the brick is fired and polished to obtain the finished gradient iridescent ceramic brick.

[0132] Comparative Example 4

[0133] A method for preparing gradient color ceramic tiles includes the following steps:

[0134] 1) Preparation of colorful particles

[0135] Labradorite ore is crushed into 4-mesh labradorite particles. The labradorite particles are treated with a treatment solution and stirred at 45°C for 100 minutes at a stirring speed of 80 r / min. After rinsing and drying, iridescent particles are obtained. The treatment solution includes the following raw materials: sulfuric acid and metal chloride solution, wherein the volume ratio of sulfuric acid to metal chloride solution is 1:1; the concentration of sulfuric acid is 1.0 mol / L, and the concentration of metal chloride solution is 1.0 mol / L.

[0136] 2) Preparation of transparent frit

[0137] Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit.

[0138] The transparent frit, by weight, comprises the following raw materials:

[0139] Potassium feldspar 20 parts, sodium feldspar 18 parts, kaolin 8 parts, calcined clay 9 parts, corundum 5 parts, diopside 7 parts, wollastonite 8 parts, lithium feldspar 9 parts, strontium carbonate 10 parts, zinc oxide 6 parts.

[0140] 3) Apply dry granular layer

[0141] Mix the iridescent particles and transparent frit particles evenly to obtain a mixture; apply the mixture to the glaze layer of the unglazed body.

[0142] 4) Firing

[0143] The unglazed body after applying the mixture is fired at 1240℃ for 70 minutes to obtain a semi-finished product of gradient colorful ceramic tile.

[0144] 5) Polishing

[0145] Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

[0146] To more clearly illustrate the importance of the iridescent particles in this application, as well as the specific process parameters and conditions, the same proportion, operating method, and dosage were used for the application of the dry particle layer, mixing of the iridescent particles and transparent frit on the ceramic tile blank; the polishing process employed a unified polishing method of coarse polishing, medium polishing, and fine polishing.

[0147] Following the above-described methods for preparing iridescent particles and frits, labradorite ore was crushed and purified. The effects of different parameter variables on the iron ion content in the iridescent particles and on yellow spots on the ceramic tile surface were investigated, using sulfuric acid concentration, metal chloride solution concentration, reaction temperature, stirring time, and rotation speed as parameters. The wear resistance, color saturation, and other properties of the microcrystalline layer on the ceramic tile surface were adjusted by adjusting the proportions of each raw material component in the transparent frit. The iridescent ceramic tiles prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests as shown in Table 1. The test results are presented in Table 1 below.

[0148] Table 1

[0149]

[0150] Note: The method of evaluating the abrasion resistance of ceramic tiles is based on the national standard GB / T 3810.7-2016 "Test Methods for Ceramic Tiles - Part 7: Determination of Abrasion Resistance of Glazed Tiles". The abrasion resistance tester is used to place abrasive media on the glazed surface and rotate it. The worn samples are observed and compared with the unworn samples to evaluate the abrasion resistance of ceramic tiles.

[0151] Analysis of the results in Table 1 shows that, assuming the particle size of the colored particles is basically the same, the performance test results of the ceramic tiles prepared in Example 1 and Comparative Example 1 indicate that after iron removal and purification of labradorite, the iron impurity content of the colored particles is reduced, and the area of ​​individual yellow spot defects on the surface of the ceramic tiles is significantly reduced. In the performance tests of Example 2 and Comparative Example 2, the stirring speed had little effect on the removal of iron impurities. In Examples 1-5, the changes in the iron impurity content of the colored particles and the area of ​​yellow spot defects on the surface of the ceramic tiles showed that the iron ion removal effect was better with increasing sulfuric acid and metal chloride concentrations. The iron ion content of the labradorite and the area of ​​yellow spot defects gradually decreased. However, after increasing the concentration of sulfuric acid and metal chloride solutions to a certain extent in Examples 4 and 5, further increases in the concentration of sulfuric acid and metal chloride solutions had little effect on the removal of iron ions.

[0152] Based on the experimental results in Table 1, and from Example 1 and Comparative Example 3, it can be concluded that: reaction time and reaction temperature have a significant impact on the iron impurity content. The comprehensive test results show that Example 3 has the best process parameters, with the lowest iron ion content, the smallest yellow spot defect area, and the highest microcrystalline layer hardness of 1500 revolutions at level 3 on the surface of the ceramic tile.

[0153] In the following examples, the volume and concentration of the treatment liquid were kept constant, and the reaction time and temperature were further adjusted, while the proportions of various raw materials for preparing the frit were also adjusted.

[0154] Example 6

[0155] The preparation steps and parameters in this embodiment are the same as in Example 3, except that: in step 1), the preparation of iridescent particles involves treating labradorite particles with a treatment solution at 40°C for 60 minutes, followed by rinsing and drying to obtain iridescent particles; in step 2), the preparation of transparent frit comprises, by weight, the following raw materials:

[0156] Potassium feldspar 25 parts, sodium feldspar 12 parts, kaolin 8 parts, calcined clay 10 parts, corundum 8 parts, diopside 6 parts, wollastonite 9 parts, lithium feldspar 10 parts, strontium carbonate 7 parts, zinc oxide 5 parts.

[0157] The prepared iridescent particles are mixed with frit particles in a certain proportion, a dry particle layer is applied to the brick blank, and then fired and polished to obtain the finished product of gradient iridescent ceramic brick.

[0158] Example 7

[0159] The preparation steps and parameters in this embodiment are the same as in Example 3, except that: in step 1), the preparation of iridescent particles involves treating labradorite particles with a treatment solution at 70°C for 70 minutes, followed by rinsing and drying to obtain iridescent particles; in step 2), the preparation of transparent frit comprises, by weight, the following raw materials:

[0160] Potassium feldspar 22 parts, sodium feldspar 12 parts, kaolin 7 parts, calcined clay 9 parts, corundum 9 parts, diopside 8 parts, wollastonite 9 parts, lithium feldspar 10 parts, strontium carbonate 6 parts, zinc oxide 8 parts.

[0161] Then, the prepared iridescent particles are mixed with the frit particles in a certain proportion, a dry particle layer is applied to the brick blank, and then the brick is fired and polished to obtain the finished product of gradient iridescent ceramic brick.

[0162] Comparative Example 5

[0163] The preparation steps and parameters in this comparative example are the same as in Example 7, except that: in step 1), the preparation of iridescent particles involves treating labradorite particles with a treatment solution at 80°C for 80 minutes, followed by rinsing and drying to obtain iridescent particles; in step 2), the preparation of transparent frit comprises, by weight, the following raw materials:

[0164] Potassium feldspar 20 parts, sodium feldspar 12 parts, kaolin 8 parts, calcined clay 10 parts, corundum 9 parts, diopside 9 parts, wollastonite 9 parts, lithium feldspar 10 parts, strontium carbonate 7 parts, zinc oxide 6 parts.

[0165] Then, the prepared iridescent particles are mixed with the frit particles in a certain proportion, a dry particle layer is applied to the brick blank, and then it is fired and polished to obtain the finished product of gradient iridescent ceramic brick.

[0166] The effects of iron removal reaction time and temperature on the iron impurity content of the colored particles during the preparation process were studied, as well as the ratio of various chemical raw materials in the calcined frit particles, on the improvement of wear resistance and color saturation. The test results of various properties are shown in Table 2 below:

[0167] Table 2

[0168]

[0169] As shown in Table 2, the iron ion content in the colorful particles decreases with increasing reaction time. Increasing the reaction time from 70 min to 80 min has no significant effect on iron removal. Increasing the reaction temperature accelerates the movement of ions and also promotes the dissolution reaction of iron. However, after reaching a certain temperature, the dissolution effect no longer improves.

[0170] Considering both energy consumption and the iron removal effect of the colorful particles, Example 7 is the optimal process scheme. At the same time, the iron ion content is reduced from 0.50% in the raw ore to 0.04%, the iron removal efficiency reaches over 90%, and the wear resistance and color saturation reach the highest level.

[0171] Therefore, the iridescent particles of this application have the following advantages:

[0172] 1. Preparation method of iridescent particles: Labradorite particles are prepared using a jaw crushing process, which preserves the original crushed texture of the stone. The natural texture of the feldspar particles can produce light interference, making the surface exhibit a gradient iridescent sapphire luster. In contrast, the spherical grinding process grinds the particle surface into an uneven frosted spherical shape. The frosted spherical surface produces diffuse reflection, and the luster cannot be focused, thus failing to form an iridescent luster pattern.

[0173] 2. Preparation method of colorful particles: During the jaw crushing process, mechanical iron powder is generated. When sieving and classifying the particle size, it is washed with clean water at the same time. This washes away small feldspar particles, as well as the mechanical iron powder attached to the feldspar particles and the dust from the original ore produced by crushing. This reduces the need for a strong magnetic separator to remove mechanical iron, and yields flaky labradorite particles between 2 and 20 mesh.

[0174] 3. Preparation method of colorful particles: Place the mixed solution of sulfuric acid and metal chloride in an ultrasonic container, add crushed flaky labradorite particles, and the ultrasonic waves in the container can accelerate the vibration of the mixed solution, so that the mixed solution can react with the iron impurities attached to the surface of the feldspar particles quickly and evenly, thereby increasing the reaction rate and reducing the reaction time.

[0175] 4. Preparation method of iridescent particles: The iron removal process of labradorite ore uses a treatment solution formed by non-volatile sulfuric acid and zinc chloride solution. Sulfuric acid can dissolve the iron in the labradorite ore into soluble iron ions. Soluble iron ions have high solubility in sulfuric acid and zinc chloride solution. Therefore, through the treatment solution, the iron in the labradorite ore can be processed into soluble iron ions. Then, through sieving and separation, labradorite particles with low iron ion content are obtained. Therefore, by using the replacement method, zinc metal chloride replaces iron ions, improving the conversion rate, and the iron leaching rate can reach more than 90%.

[0176] Experimental Study 2

[0177] A method for preparing gradient iridescent ceramic tiles involves using iridescent particles as a dry granule layer raw material in the preparation of ceramic tiles. The specific process includes the following steps:

[0178] Step 1: Preparation of flaky, iridescent particles after removing impurities;

[0179] Step 2: Mix the chemical raw materials potassium feldspar, sodium feldspar, kaolin, calcined clay, corundum, diopside, wollastonite, lithium feldspar, strontium carbonate, and zinc oxide in a certain proportion and calcine them at a high temperature of 1450-1650℃ to form a transparent frit for later use.

[0180] Step 3: Prepare conventional ceramic clay powder, dry press it into shape using a Henglitai YP5009 press to press it into 600×1200mm ceramic brick blanks. Dry the brick blanks in a drying kiln at 150-220℃ for 60-90 minutes to form unglazed bricks for later use.

[0181] Step 4: Spray a small amount of clean water onto the surface of the unglazed brick to moisten it, enhancing the adhesion between the body and the glaze. Apply a top coat of glaze to the surface of the brick using a vertical glazing applicator, with a glaze application rate of 400-500 g / m². 2 It is applied to the surface of the ceramic body, which can cover the color of the body, enhance the whiteness of the ceramic tile glaze, and improve the decorative effect of marble patterns.

[0182] Step 5: Multi-channel inkjet printing of marble design patterns and process effect inks to decorate the surface of the brick blank, enhancing the design and three-dimensional aesthetics of the brick surface stone.

[0183] Step 6: Screen printing protective glaze. A transparent protective glaze is printed on the surface of the ceramic tile blank using a 100-mesh screen to protect the marble design pattern from being damaged by molten particles in subsequent processes.

[0184] Step 7: Mix the colorful particles and transparent frit particles evenly according to the design requirements by mass ratio, and transport them to the dry granulator via conveyor belt, and evenly apply them to the brick blank that has been printed with protective glaze.

[0185] Step 8: Evenly spray adhesive onto the ceramic tile blank with frit particles using a spray gun. The amount of adhesive used is 200-300g / m². 2 After drying in a drying oven at 180-230℃ for 3-5 minutes, the glue sprayed on the surface of the brick body during drying plays a role in bonding and fixing the surface frit particles. This ensures that the colorful particles and frit particles remain fixed on the surface of the brick body and do not fall off during the production line operation and roller kiln firing process.

[0186] Step 9: Roller kiln firing. The preheating zone at the front end raises the temperature of the brick blanks and removes the remaining free water and structural water in the raw materials. This prevents the brick blanks from cracking due to excessively rapid heating and water removal in the kiln firing zone. After being fired at a high temperature of 1220-1250℃ in the roller kiln, the frit particles soften and melt, and combine with the iridescent particles to form a microcrystalline glass layer of a certain thickness. After being cooled in the roller kiln cooling zone, a semi-finished product of gradient iridescent ceramic bricks is formed.

[0187] Step 10: After firing the semi-finished gradient iridescent ceramic tiles, polish them. Some iridescent particles may have slight dot-like protrusions. The polishing process can make the iridescent particles and the microcrystalline glass layer smooth and shiny, and the ceramic tiles will show a gradient iridescent luster of different sizes.

[0188] Polishing process: The polishing machine's grinding head is equipped with diamond and silicon carbide modules, and polishing is carried out in three stages: rough polishing, medium polishing, and fine polishing. In the rough polishing stage, 10 sets of 500-grit and 10 sets of 800-grit diamond modules are installed to initially grind and level the slightly uneven iridescent particles and transparent microcrystalline layer. In the medium polishing stage, 10 sets of 1000-grit and 10 sets of 1500-grit silicon carbide modules are used to more thoroughly and delicately grind the microcrystalline layer and iridescent particles, removing scratches from the rough polishing and improving flatness. Finally, in the fine polishing stage, 10 sets of 2000-grit and 10 sets of 3000-grit silicon carbide modules are used to polish and brighten the surface of the ceramic tile. A sponge is used to apply super-clean and bright wax, and the surface of the iridescent particles forms a bright mirror surface. From different angles, it will have different brightness and a gradient iridescent blue gemstone-like metallic luster.

[0189] Specifically, in step 7, the fineness of the transparent frit particles is 8-30 mesh. The transparent frit is fixedly selected from the frit prepared with the optimal ratio in Example 7 of the study, and includes the following raw materials in parts by weight:

[0190] Potassium feldspar 22 parts, sodium feldspar 12 parts, kaolin 7 parts, calcined clay 9 parts, corundum 9 parts, diopside 8 parts, wollastonite 9 parts, lithium feldspar 10 parts, strontium carbonate 6 parts, zinc oxide 8 parts.

[0191] Specifically, the powder used for the ceramic body can be any commercially available conventional ceramic tile powder. Here, a set of raw materials is provided for the preparation of ceramic tiles in the following embodiments. By mass percentage, the chemical composition of the raw material powder includes: SiO2 66.15%, Al2O3 20.46%, Fe2O3 0.57%, TiO2 0.14%, CaO 0.56%, MgO 0.95%, K2O 3.68%, Na2O 2.71%, and loss on ignition 4.78%.

[0192] Specifically, the iron removal and purification process of labradorite ore and the raw materials of each component of the transparent frit were carried out according to the best embodiment 7 in Experimental Study 1. The fine crushing process of labradorite can be divided into two processing methods: ball grinding and jaw crushing. The effects of process parameters such as particle size, the mixing of the purified iridescent particles into the frit glaze layer, the thickness of the material applied to the brick blank, and the polishing method after firing the semi-finished product on the gradient iridescent gloss were tested.

[0193] Example 8

[0194] The fine crushing stage of the labradorite ore is carried out using a jaw crusher to crush it into 20-30 mesh flaky particles. After iron removal and purification, it is mixed with frit particles in a fixed ratio and evenly applied to the surface of the brick blank with a thickness of 1.0-1.5mm. The resulting ceramic brick semi-finished product is then fired. The polishing process uses coarse polishing, medium polishing, and fine polishing to produce the finished gradient and colorful ceramic brick.

[0195] Example 9

[0196] The fine crushing stage of the labradorite ore is carried out using a jaw crusher to crush it into 100-200 mesh flaky particles. After iron removal and purification, it is mixed with frit particles in a fixed ratio and evenly applied to the surface of the brick blank with a thickness of 0.5-1.0 mm. It is then fired into a semi-finished ceramic brick. The polishing process uses coarse polishing, medium polishing and fine polishing to produce the finished gradient colorful ceramic brick.

[0197] Example 10

[0198] The fine crushing stage of the labradorite ore is carried out using a jaw crusher to crush it into 6-20 mesh flaky particles. After iron removal and purification, it is mixed with frit particles in a fixed ratio and evenly applied to the surface of the brick blank with a thickness of 1.5-2.5mm. The resulting ceramic brick semi-finished product is then fired. The polishing process uses coarse polishing, medium polishing, and fine polishing to produce the finished gradient and colorful ceramic brick.

[0199] Example 11

[0200] The fine crushing stage of the labradorite ore is carried out using a jaw crusher to crush it into 2-8 mesh flaky particles. After iron removal and purification, it is mixed with frit particles in a fixed ratio and evenly applied to the surface of the brick blank with a thickness of 2.5-3.0mm. The resulting ceramic brick semi-finished product is then fired. The polishing process uses coarse polishing, medium polishing, and fine polishing to produce the finished gradient and colorful ceramic brick.

[0201] Comparative Example 6

[0202] The conditions in this comparative example are the same as those in Example 8, except that the fine crushing stage of the labradorite ore adopts a ball-grinding process, which grinds the feldspar into 20-30 mesh and then grinds it into particles with a spherical frosted surface.

[0203] Comparative Example 7

[0204] The conditions in this comparative example are the same as those in Example 8, except that the polishing process does not include coarse polishing, but only medium and fine polishing processes to produce the finished gradient colored ceramic tile.

[0205] To more clearly illustrate the preparation method of the gradient iridescent ceramic tiles of this application, the above preparation steps and process parameters all adopt the optimal process parameter scheme of Example 7 in Experimental Study 1, and are carried out under the same conditions. Only the key steps and parameters are adjusted to more clearly and concisely describe the iridescent effect.

[0206] 1) The same coarse and medium crushing processes are used for labradorite ore, with adjustments only made to the fine crushing method and particle size; 2) The thickness of the frit glaze layer is adjusted according to the size of the iridescent particles; 3) For the polishing process, only the first stage of coarse polishing is used to initially grind and even out the slightly uneven iridescent particles and transparent microcrystalline layer, and to study the gradient iridescent effect. Since the medium and fine polishing stages do not significantly affect the iridescent effect and only serve to polish and brighten, the same polishing method is used for both medium and fine polishing without adjustment.

[0207] According to the above-mentioned method for preparing gradient iridescent ceramic tiles, the processing method of fine crushing of labradorite ore, the size of iridescent particles after fine crushing and purification, the thickness of the glaze layer of the frit, and the polishing method are used as parameters. At the same time, the influence of different parameter variables on the size of the iridescent effect of a single iridescent particle on the surface of the ceramic tile and the iridescent effect presented by a single iridescent particle are investigated. The finished gradient iridescent ceramic tiles prepared in Examples 8-11 and Comparative Examples 6-7 are subjected to the performance tests shown in Table 3. The relevant results are summarized in Table 3.

[0208] Table 3

[0209]

[0210] Comparative tests in Examples 8 and 9 show that the finer the iridescent particles, the less visible the iridescent luster becomes when ground into powder. Therefore, large-particle labradorite is required, and the larger the particles, the more pronounced the gradient iridescent effect. A comparison between Example 8 and Comparative Example 6 shows that for the same particle size, the crushing process yields a better iridescent effect than the spherical grinding method, resulting in a larger iridescent effect per particle and a higher proportion of particles with iridescent luster. A comparison between Example 8 and Comparative Example 7 shows that the polishing process, which involves coarse polishing followed by medium and fine polishing, results in a larger iridescent effect per particle and a higher proportion of particles exhibiting iridescent luster. Analysis of the test results from Examples 8-11 indicates that under the same crushing and polishing conditions, the smaller the mesh size of the flaky iridescent particles (i.e., the larger the particle size), the better the iridescent effect and the higher the proportion of iridescent luster per particle.

[0211] Therefore, Example 11 can be applied to ceramic tile products to achieve a sapphire blue gradient iridescent luster effect on the tile surface, similar to that of natural stone. The larger the iridescent particles, the larger the area of ​​the gradient iridescent luster that a single particle will exhibit after polishing, closely resembling the gradient iridescent metallic luster of sapphire. Furthermore, the particle size can be randomly matched, resulting in a higher degree of realism compared to natural luxury stone. The research and development of ceramic tiles using this process can reduce the mining of precious stones and protect the natural ecological environment.

[0212] The aforementioned gradient iridescent ceramic tiles are fired at 1220-1250℃, resulting in a stable chemical structure, high wear resistance, high temperature resistance, and aging resistance. The iridescent particles fuse well with the fused particles after high-temperature firing, making the structure less prone to damage. Durability tests and trampling tests have verified a service life of 30-40 years. Gradient iridescent ceramic tiles can be used in interior decoration, specifically for walls and floors in villas, office buildings, high-end hotel lobbies, conference rooms, and clubs. They enhance the decoration, making each tile exude elegance, luxury, and a sophisticated atmosphere, reflecting high taste.

[0213] The above embodiments are preferred implementations of the present invention. In addition, the present invention can be implemented in other ways. Any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A gradient color ceramic tile, comprising a bisque, a glaze layer disposed on the bisque, and a dry granule layer disposed on the glaze layer; characterized in that, The dry granule layer includes iridescent particles and transparent frit; the iron ion content in the iridescent particles is ≤0.04%; the thickness of the dry granule layer is 2.5-3.0 mm; the dry granule layer is subjected to coarse polishing, medium polishing and fine polishing. The iridescent particles are obtained by treating labradorite ore with a processing solution. The treatment solution comprises the following raw materials: sulfuric acid and a metal chloride solution, wherein the volume ratio of the sulfuric acid to the metal chloride solution is 1:1; the concentration of the metal chloride solution is 1.5 mol / L; and the concentration of the sulfuric acid is 2 mol / L. The labradorite ore is crushed into 2-6 mesh flaky labradorite particles, and the flaky labradorite particles are treated with a processing solution to obtain iridescent particles. The treatment conditions for the liquid were stirring at 70°C for 70 minutes.

2. The gradient color ceramic tile according to claim 1, characterized in that, The solute in the metal chloride solution is any one or more of zinc chloride, magnesium chloride, and calcium chloride.

3. The gradient color ceramic tile according to claim 1, characterized in that, The transparent frit, by weight, comprises the following raw materials: Potassium feldspar 14-30 parts, sodium feldspar 8-22 parts, kaolin 6-10 parts, calcined clay 4-12 parts, corundum 2-10 parts, diopside 6-10 parts, wollastonite 6-12 parts, lithium feldspar 8-14 parts, strontium carbonate 4-10 parts, zinc oxide 2-10 parts.

4. The method for preparing gradient iridescent ceramic tiles according to any one of claims 1-3, characterized in that, Includes the following steps: 1) Preparation of colorful particles Labradorite ore is treated with a processing solution to obtain iridescent particles; 2) Preparation of transparent frit Prepare the corresponding raw materials according to the weight composition of the transparent frit; mix the raw materials and fire them into a transparent frit. 3) Apply dry granular layer Mix the iridescent particles and transparent frit particles evenly to obtain a mixture; apply the mixture to the glaze layer of the unglazed body. 4) Firing The unglazed body after applying the mixture is fired to obtain a semi-finished product of gradient colorful ceramic tile. 5) Polishing Semi-finished colored ceramic tiles are polished to obtain finished colored ceramic tiles with gradient patterns.

5. The preparation method according to claim 4, characterized in that, In step 4), the firing temperature is 1220-1250℃, and the firing cycle is 65-80 minutes.

6. An application of gradient color ceramic tiles, characterized in that, The gradient colored ceramic tile as described in any one of claims 1-3 or the gradient colored ceramic tile prepared by the preparation method described in any one of claims 4-5 shall be applied to the decoration field.

Citation Information

Patent Citations

  • Method using sulfuric acid and metal chloride media to remove iron in order to purify quartz sands

    CN108298545A

  • Ceramic product with halo glaze effect and preparation method thereof

    CN116425415A